CROP WILD RELATIVES OF THE AKTOBE FRORAL DISTRICT - S. A. Aipeisova (Труды по прикладной ботанике, генетике и селекции)
For the first time crop wild relatives have been found and recorded in the Aktobe floral district. They have been catalogued in a summary of crop wild relatives which includes data on 412 species. For Secale sylvestre, a natural focus of habitation has been discovered.